2017
DOI: 10.1016/j.jpedsurg.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Manometric findings in relation to functional outcomes in different types of anorectal malformations

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Mild sacral dysplasia (3-4 segments remaining) may not impact significantly on the prognosis for fecal continence, prevalence of lower urinary tract symptoms, or sexual function according to recent analyses. 16,17,45 The presence of functional IAS on anorectal manometry, as indicated by a positive rectoanal inhibitory reflex (RAIR) postoperatively, has been associated with improved functional outcomes. 29,45 This finding favours conserving the distal part of the fistula in severe ARMs in association with sagittal repairs.…”
Section: Other Important Prognostic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mild sacral dysplasia (3-4 segments remaining) may not impact significantly on the prognosis for fecal continence, prevalence of lower urinary tract symptoms, or sexual function according to recent analyses. 16,17,45 The presence of functional IAS on anorectal manometry, as indicated by a positive rectoanal inhibitory reflex (RAIR) postoperatively, has been associated with improved functional outcomes. 29,45 This finding favours conserving the distal part of the fistula in severe ARMs in association with sagittal repairs.…”
Section: Other Important Prognostic Factorsmentioning
confidence: 99%
“…16,17,45 The presence of functional IAS on anorectal manometry, as indicated by a positive rectoanal inhibitory reflex (RAIR) postoperatively, has been associated with improved functional outcomes. 29,45 This finding favours conserving the distal part of the fistula in severe ARMs in association with sagittal repairs. RAIR was preserved in 100% of mild ARMs and 83% of severe ARMs (including 70% of males with RUF after PSARP) in the authors' recent evaluation.…”
Section: Other Important Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results have been contradictory and with dubious clinical value. Some studies have found a correlation between the extent of sphincter damage and the degree of continence and others have not 5 . Three-Dimensional High Resolution anorectal manometry (3D-HRAM) is a technique providing an image of the pressure profile of the sphincter complex.…”
mentioning
confidence: 99%
“…The manometry systems used in different centers were products of the same company (Medical Measurement Systems [MMS]) and the parameters concerned in this study (sphincteric resting / squeezing pressure and anorectal sensation) were measured in the same way among the three centers. Combining the data from two previous studies regarding the manometric findings in pediatric population as well as the values from six age-matched healthy children recruited for another study, the reference values for normal sphincteric resting pressure was 30 mm Hg to 60 mm Hg and squeezing pressure was 50 mmHg to 120 mmHg [8,9]. Anorectal sensation was recorded by distending the balloon with various volume of air.…”
Section: Anorectal Manometrymentioning
confidence: 99%